Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11031-015-9502-1
|View full text |Cite
|
Sign up to set email alerts
|

Testing the convergent and discriminant validity of three implicit motive measures: PSE, OMT, and MMG

Abstract: Implicit motive research has shown that implicit motives are important predictors of behavior and well-being. However, little is known about the interrelationship between the different implicit motives measures frequently applied. We aimed to shed light on the convergent validity of three implicit motive measures and wanted to test their assumed statistical independence from three explicit motive measures. Therefore, we administered the picture story exercise (PSE), the operant motive test (OMT), and the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 87 publications
1
57
0
1
Order By: Relevance
“…For example, the convergent validity of the measure was supported by significant correlations of the OMT motive scores with PSE motive scores coded according to Winter (1994;Scheffer. 2001) when arousing the respective motives experimentally (power r = .47, p < .001; achievement r = .47, p < .001; affiliation r = .31, p < .05; note that correlations are lower without motive arousal, Schüler, Brandstätter, Wegner, & Baumann, 2015). Previous work has also demonstrated that implicit motives as measured by the OMT were able to successfully predict behavior (cf.…”
Section: The Present Investigationmentioning
confidence: 88%
“…For example, the convergent validity of the measure was supported by significant correlations of the OMT motive scores with PSE motive scores coded according to Winter (1994;Scheffer. 2001) when arousing the respective motives experimentally (power r = .47, p < .001; achievement r = .47, p < .001; affiliation r = .31, p < .05; note that correlations are lower without motive arousal, Schüler, Brandstätter, Wegner, & Baumann, 2015). Previous work has also demonstrated that implicit motives as measured by the OMT were able to successfully predict behavior (cf.…”
Section: The Present Investigationmentioning
confidence: 88%
“…For several reasons, we chose not to employ such a picture-based task in this study. First, the coding of such story tasks is often rather time-consuming and requires a high level of expertise (Sch€ uler, Brandstäter, & Wegner, 2015). Additionally, these tasks involve very different stimuli (i.e., ambiguous pictures) than explicit measures of need strength (i.e., structured questions), which limits the comparability between implicit and explicit measures (Brunstein & Schmitt, 2004).…”
Section: S Tudymentioning
confidence: 99%
“…Footnotes 1 Contemporary motive measures that did not meet these criteria and whose conceptual and empirical convergence with PSE-type implicit motive measures has been questioned in recent research include the Operant Motive Test and the Multi-Motive Grid (see Schüler, Brandstätter, Wegner, & Baumann, 2015;Schultheiss, Dirlikov, Yankova, & Schad, 2009). …”
Section: Acknowledgmentmentioning
confidence: 99%